Agricultural Products' Custom Bundling Pricing Based on Positive Externality. (September 2020) - Wang, L; Pan, Y; Sun, X
Abstract: Agriculture, rural and farmers are world-wide issues, and agricultural products have long been a problem for China's "agriculture, rural and farmers". Because agricultural products show strong positive externality, the formulation of bundled pricing strategy can not only reflect the characteristics of agricultural products, but also in line with the development trend of Chinese agriculture. This paper studies the pricing of product bundles under positive externality- with agricultural products as the object, combined with the pricing of agricultural products, and discusses the situation of custom bundled pricing of agricultural products under positive externality, and provides reference to the custom bundled pricing strategies of agricultural products for rural areas, agriculture and farmers in China.